SISTEM INFORMASI MANAJEMEN BERBASIS UML (STUDI KASUS PEMELIHARAAN TOILET PADA KAMPUS FAKULTAS TEKNIK UNIVERSITAS LAMBUNG MANGKURAT) - Yuslena Sari; Irfan Prasetia (Fakultas Teknik Universitas Lambung Mangkurat, 2016)
This paper presents concept of a database system on a computer software systems. Requirements in analysis and design are a serious problem in developing a manual system into a computer software system that is fully automated. To link the two systems (manual and automatic), a modeling language Unified Modeling Language (UML) is now accepted as the de facto standard for the design and specification of object-oriented systems. In this study, ULM modeling language used to design a management information system (MIS) of Toilet Maintenance on the Faculty of Engineering, Lambung Mangkurat University using Access 2013. From this system, dean as admin of the system, can immediately know the damage or the need of maintenance in real time every day. Such information would greatly assist the management on making decision related to monitoring, maintenance and repair of toilet in the Faculty of Engineering, Lambung Mangkurat University. The final results is to keep the cleanliness and reliability of toilet in the Faculty of Engineering, Lambung Mangkurat University.